Pengaruh Keterampilan Bahasa Inggris Terhadap Kesiapan Kerja Mahasiswa D4 Manajemen Perhotelan Pada Industri Perhotelan - Muhammad Zikri Efendi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research is to explore how English language skills impact the work readiness of students. This study is classified as quantitative research. The focus is on all students from the Hospitality Management program at the State University of Padang, specifically those from the class of 2021 who have completed both their first and second internships. The research sample consists of 64 respondents. Data was collected through a questionnaire that was distributed to the participants.For data analysis, several techniques were used, including descriptive analysis of the respondents' data, descriptive analysis of the variables, and partial least squares analysis.The findings reveal that English language skills have a significant influence on work readiness, with an R-squared value of 0.632. This indicates that English language skills explain 63.2% of the variation in work readiness. The T-statistic was found to be 14.704, and the p-value was 0.000, which is below the 0.05 threshold. This allows us to accept the hypothesis that “There is a significant influence of English language skills on the work readiness of Hospitality Management students in the hospitality industry.” Furthermore, the analysis shows that English language skills have a notably positive effect on work readiness, as indicated by the Original Sample (O) value of 0.795.